Development and performance evaluation of a chapati processing machine - AKHILA J. CHAND RASMI JANARDHANAN SANAD S SANDHYA K.R; Dr. Prince M.V (Guide) (Tavanur 2015 Department of f Food and Agricultural Process Engineering)
Development and performance evaluation of a chapati processing machine
Development and performance evaluation of a chapati processing machine